Pengaruh Kualitas Pelayanan terhadap Kepuasan Mahasiswa Program Ekstensi Fakultas Ekonomi Universitas Jambi - Yenny Yuniarti (Faculty of Economics and Business, University of Pasundan, 2014)
The phenomenon happening nowadays is that, colleges become commodities needed by society in order to improve people’s lives. A quality college is literally seen by the public from its facilities and infrastructures as well as by the satisfaction of the students at that college or university. So the purpose of this study is to observe the effect of service quality on student satisfaction at the Extension Program Faculty of Economics, University of Jambi, either simultaneously or partially. The data used are primary and secondary data. Primary data were obtained from questionnaires disseminated to 100 students which were selected as research sample. The method used is descriptive method of verification, while the research tool used is path analysis. The result of this research shows that there is significant effect of service quality on student satisfaction both simultaneously (by 54.2%) and partially. The partial effect on reliability is 19.98%, responsiveness is 23.25%, physical evidence is 25.34%, empathy is 21.57%, and assurance is 18.10%.